Fast-Fourier-based error propagation for the gravimetric terrain correction - McCubbine, Jack; Featherstone, Will; Kirby, Jon (Society of Exploration Geophysics, 2017)
We have identified a gap in the literature on error propagation in the gravimetric terrain correction. Therefore, we have derived a mathematical framework to model the propagation of spatially correlated digital elevation model errors into gravimetric terrain corrections. As an example, we have determined how such an error model can be formulated for the planar terrain correction and then be evaluated efficiently using the 2D Fourier transform. We have computed 18.3 billion linear terrain corrections and corresponding error estimates for a 1 arc-second (~30 m) digital elevation model covering the whole of the Australian continent.